Thwaites Glacier ice surface elevation change, December 2013 to July 2017, and July 2017 to November 2020 - Bevan, Suzanne; Luckman, Adrian; Benn, Douglas (NERC EDS UK Polar Data Centre, 2021)
Two maps of surface elevation change for Thwaites Glacier, West Antarctica. Change is in metres between 2013-12-21 and 2017-07-11, and between 2017-07-11 and 2020-11-02. The work was funded by NERC projects NE/P011365/1 and NE/S006605/1. : The initial digital elevation models (DEMs) were created via an interferometric analysis of TanDEM-X satellite system synthetic aperture radar data. Phase-scaling utilised the supplied orbit data. The DEMs were geocoded first using the RAMP DEM (Liu et al., 2015) and then, iteratively, using the DEMs themselves. The DEMs were calibrated in the vertical using an ICESat-2 point at (107.49°W, 75.47°S) acquired on 2018-11-05. Processing is described fully in the reference paper. : Interferometric analysis was carried out using Gamma Remote Sensing software 20190603. : Via comparison with ICESat-2 data and in consideration of orbit uncertainty, the original DEMs have an estimated vertical uncertainty of ±3 m, the difference therefore has an estimated uncertainty of ±4.2 m.